Interaction of childhood trauma with rs1360780 of the FKBP5 gene on trait resilience in a general population sample. (September 2019) - Terock, Jan; Van der Auwera, Sandra; Hannemann, Anke; Janowitz, Deborah; Homuth, Georg; Teumer, Alexander; Grabe, Hans Jörgen
Highlights: Main and interactive effects of childhood trauma and FKBP5 on resilience were tested in a general-population sample. Childhood trauma and all subscales were negatively associated with trait resilience. Rs1360780 showed no main effects on resilience. Childhood trauma and rs1360780 interacted such that the T-allele enhanced effects of childhood trauma on resilience. Effects remained stable even after adjusting for depression and PTSD.